Reality or Appearance of Ethical Life? - Honneth , Axel (ETHICS IN PROGRESS, 2022)
The article attempts to show that Hegel’s concept of “civil society” is characterized by a deep ambivalence about the value of the new market economy. On the one side, Hegel believed that the economic system represented by “civil society” succeeded like no other in simultaneously giving free reign to the desires of individual subjects and integrating them into a stable structural framework (I). On the other side, Hegel’s reflections are growingly overtaken by doubts as to whether, in light of its self-destructive tendencies, the market system can be as successful in guaranteeing individual freedom as he first envisaged it to be (II). In the course of this essay, it will ultimately become clear that Hegel’s attempt to redefine “civil society” reveals considerably more conceptual indecision and inner conflict than one might have suspected from the great system builder.